2021
DOI: 10.1111/edt.12682
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic markers of post‐traumatic dental external root resorption in children—a pilot study

Abstract: Background External inflammatory root resorption (EIRR) is a frequent complication of traumatic dental injuries (TDI). The aim of this cohort study was to identify novel non‐invasive markers of post‐traumatic EIRR by assessing the changes in the pulp's blood flow and the composition of gingival sulcus fluid (GCF) in children after dental trauma. Material and methods Thirty‐two children were enrolled and assessed within 48 h of a TDI to their permanent incisors and during an additional three visits over a 6‐mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“… 16 In another study, Maga et al investigated IL‐1α and found significantly higher levels in the injured teeth with EIRR at the second, third and fourth visits. The same was seen when the levels were compared between the injured teeth with EIRR and those without ERRR 17 . Diminished values were recorded with LDF in injured teeth with EIRR compared with the control teeth at all visits.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“… 16 In another study, Maga et al investigated IL‐1α and found significantly higher levels in the injured teeth with EIRR at the second, third and fourth visits. The same was seen when the levels were compared between the injured teeth with EIRR and those without ERRR 17 . Diminished values were recorded with LDF in injured teeth with EIRR compared with the control teeth at all visits.…”
Section: Resultssupporting
confidence: 57%
“…Diminished values were recorded with LDF in injured teeth with EIRR compared with the control teeth at all visits. A lower level was seen in injured teeth without EIRR than in the control teeth at the first two visits and a higher level in the control teeth than in the injured teeth at the third and fourth visits 17 . The sensitivity for EIRR was 0.72, and specificity was 0.28 17 .…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Even though EIR is primarily a radiologic diagnosis, a clinical diagnostic approach seems conceivable. Two recent studies identified IL‐1α in the gingival sulcus fluid of affected teeth as a potential biomarker for EIR (Gregorczyk‐Maga et al, 2019, 2021). Further research is needed to evaluate the clinical usefulness of biomarker‐based diagnostic tests for this specific type of root resorption.…”
Section: Endodontic Management In Cases Of External Infection‐related...mentioning
confidence: 99%